Genomic Instabilities, Cellular Senescence, and Aging: In Vitro, In Vivo and Aging-Like Human Syndromes - Lidzbarsky, Gabriel; Gutman, Danielle; Shekhidem, Huda Adwan; Sharvit, Lital; Atzmon, Gil (Frontiers in Medicine, 2018)
As average lifespan and elderly people prevalence in the western world population is gradually increasing, the incidence of age-related diseases such as cancer, heart diseases, diabetes, and dementia are increasing, bearing social and economic consequences globally. Understanding the molecular basis of aging-related processes can help extend the organism's health-span, i.e. the life period in which the organism is free of chronic diseases or decrease in basic body functions. During the last decades immense progress was made in the understanding of major components of aging and healthy aging biology, including genomic instability, telomere attrition, epigenetic changes, proteostasis, nutrient sensing, mitochondrial dysfunction, cellular senescence, stem cell exhaustion and intracellular communications. This progress has been made by three spear headed strategies: in-vitro (cell and tissue culture from variety of sources), in-vivo (includes diverse model and non-model organisms), both can be manipulated and translated to human biology and the study of aging-like human syndromes and human populations. Herein we will focus on current repository of genomic “senescence" stage of aging which includes health decline, structural changes of the genome, faulty DNA damage response and DNA damage, telomere shortening and epigenetic alterations. Although aging is a complex process, many of the “hallmarks” of aging are directly related to DNA structure and function. This review will illustrate the variety of these studies, done in in-vitro, in-vivo and human levels, and highlight the unique potential and contribution of each research level and eventually the link between them.